Plant extract-based diets differently modulate immune responses and resistance to bacterial infection in striped catfish (Pangasianodon hypophthalmus). Issue 92 (September 2019) - Nhu, Truong Quynh; Bich Hang, Bui Thi; Bach, Le Thi; Buu Hue, Bui Thi; Quetin-Leclercq, Joëlle; Scippo, Marie-Louise; Phuong, Nguyen Thanh; Kestemont, Patrick
Abstract: A feeding trial was performed to compare the effects of five ethanol herbal extracts (bhumi amla, Phyllanthus amarus Schum and Thonn [Pa]; guava, Psidium guajava L. [Pg]; sensitive plant, Mimosa pudica L. [Mp]; neem, Azadirachta indica A. Juss [Ai] and asthma plant, Euphorbia hirta L. [Eh]) on the immune response and disease resistance against Edwardsiella ictaluri infection of striped catfish ( Pangasianodon hypophthalmus ) . Fish were fed diets supplemented with two doses of each plant extract (0% [basal diet], 0.4% Eh [Eh0.4], 2.0% Eh [Eh2.0], 0.2% Pa [Pa0.2], 1.0% Pa [Pa1.0], 0.2% Pg [Pg0.2], 1.0% Pg [Pg1.0], 0.4% Mp [Mp0.4], 2.0% Mp [Mp2.0], 0.4% Ai [Ai0.4], 2.0% Ai [Ai2.0]) for 8 weeks. Results showed that hematological parameters (total red blood cells, white blood cells, lymphocytes, monocytes, and neutrophils) of fish fed extract-based diets were significantly higher than in those fed the control diet ( p <  0.05) after 4 and 8 weeks. Plasma lysozyme activity increased in fish whose diets contained both doses of Eh ( p <  0.05) in week 4 (W4), whereas lysozyme activity increased in fish fed 0.2% Pa and Pg, and 2.0% Ai and Eh ( p <  0.05) in week 8 (W8). The lysozyme levels in skin mucus did not significantly differ between treatments ( p >  0.05) in W4 and after the bacterial challenge test. At the end of the feeding trial, levels of ACH50 significantly increased in most of extract groups compared to the control group ( p <  0.05). Total immunoglobulin increased considerably in both the plasma and skin mucus of fish fed extract-supplemented diets after 8 weeks. In addition, dietary supplementation with Pg, Mp, Pa0.2, Eh2.0, and Ai0.4 for 8 weeks considerably reduced the cumulative mortality against E. ictaluri infection in striped catfish. The results suggest that plant extracts possibly modulate the striped catfish immune response in a time and dose dependent manner. Specifically, diets enriched with extracts of P. guajava at 0.2 and 1.0%, or M. pudica at 2.0% for 8 weeks, have great potential for improving striped catfish health by enhancing the immune system and reducing mortality against bacterial challenges. Highlights: Plant extract-based diets possibly modulate immune responses in time and dose dependent manners. Extract-based diets differentially enhanced the immune parameters in plasma and skin mucus. Hematological parameters were improved in striped catfish following extract-based diets. Striped catfish strongly increased resistance to Edwardsiella ictaluri after feeding plant extracts. P . guajava and M. pudica strongly improved immune responses and reduced the mortality in fish infected by E. ictaluri.